1999
DOI: 10.1016/s0550-3213(98)00778-0
|View full text |Cite
|
Sign up to set email alerts
|

Finiteness of 2D topological BF-theory with matter coupling

Abstract: Abstract. We study the ultraviolet and the infrared behavior of 2D topological BF-Theory coupled to vector and scalar fields. This model is equivalent to 2D gravity coupled to topological matter. Using techniques of the algebraic renormalization program we show that this model is anomaly free and ultraviolet as well as infrared finite at all orders of perturbation theory.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Using the operators {D ± I } defined in (4.17), we may impose two types of chiral conditions. The first type is given as follows: 26) which are essentially equivalent to the previous chiral conditions (3.56) and (3.66), respectively. Here we propose to impose other type of chiral conditions…”
Section: Vector Superfield and Gauge Symmetry For N = 4 Twisted Susy mentioning
confidence: 99%
See 1 more Smart Citation
“…Using the operators {D ± I } defined in (4.17), we may impose two types of chiral conditions. The first type is given as follows: 26) which are essentially equivalent to the previous chiral conditions (3.56) and (3.66), respectively. Here we propose to impose other type of chiral conditions…”
Section: Vector Superfield and Gauge Symmetry For N = 4 Twisted Susy mentioning
confidence: 99%
“…It was later stressed that a (pseudo) scalar SUSY was also accompanied together with BRST and vector SUSY [21]. Then there appeared many related works [22][23][24][25][26][27][28][29][30] [ [31][32][33][34]. The connection of the extended SUSY and the quantization procedure of anti-field formalism by Batalin and Vilkovisky was also investigated [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…This action has not only the BRST symmetry (2.9), but also has two more fermionic symmetries [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] as shown in the following table 1. We can see that these operators …”
Section: N=d=2 Super Bf From Quantized Bf Theorymentioning
confidence: 99%
“…The BF-models have been widely investigated since the middle of the eighties [1][2][3][4][5][6][7][8][9][10][11][12], specially the two-dimensional BF-model in connection with topological quantum gravity [1][2][3][4]. The properties of ultraviolet and infrared perturbative finiteness of the two-dimensional BF-model have been rigorously proved in the framework of algebraic renormalization [5], there the authors make use of an additional symmetry peculiar to topological models in the Landau gauge, called vector-supersymmetry [6,[13][14][15].…”
mentioning
confidence: 99%
“…As a natural extension of the two-dimensional case, it has been proposed in [3] an extended BF-model, as a gauge theory for topological quantum gravity, which accommodates a topological matter coupling. Later, the authors of [7] have been shown that the model proposed in [3] is still ultraviolet and infrared finite at all orders in perturbation theory by using the same approach as those of [5] have done to the pure two-dimensional BF-model.…”
mentioning
confidence: 99%